DINAMIKA SOCIAL PROTECTION POLICY: KEBIJAKAN PEMBERLAKUAN PEMBATASAN KEGIATAN MASYARAKAT (PPKM) ERA PANDEMI COVID-19 DI INDONESIA - Revienda Anita Fitrie; Vidya Imanuari Pertiwi; Ghulam Maulana Ilman; Monalisa - (Universitas Halu Oleo, 2022)
This article aims to explore the dynamics of the Policy for the Enforcement of Community Activity Restrictions (PPKM) as a form of Social Protection Policy. The increase in Covid-19 cases in Indonesia requires the government to take quick action through the Emergency PPKM policy. Indonesia's entry into the 2nd wave of Covid-19 was marked by a significant increase in new additional cases in early July 2021. The implementation of this PPKM then gave rise to various vertical and horizontal dynamics and conflicts in the public sphere which are interesting for further review. This study uses descriptive qualitative methods with secondary data collection techniques. Data acquisition is also supported through search results from Google Mobility and Google Trends to strengthen the analysis results. The results of this study explain that the PPKM policy was officially taken by the government to suppress the spread of Covid-19 in Indonesia. Its application has proven to be effective in suppressing community mobility. The implementation of PPKM led to panic buying, increased demand for health products, to health facilities such as hospitals and health centers. The implementation of PPKM raises pros and cons, starting from the acceleration of vaccination, the use of the Peduli Protect application, integrated social welfare data to the emergence of the airport mafia. keywords: Covid-19; PPKM; Social Protection Policy;